Factors Associated with Pelvic Organ Prolapse in Eastern Region of Nepal: A Case Control Study - Joshi, Dharti; Jha, Nilambar; Sharma Paudel, Ishwari; Regmi, Mohan Chandra; Chakravartty, Avaniendra (Journal of Nepal Health Research Council, 2020)
Background: Pelvic organ prolapse is a significant public health problem in Nepal affecting a large number of women. This study was carried out to identify the factors associated with pelvic organ prolapse among the women of eastern part of Nepal. Methods: This was a matched case–control study. Cases were women aged ?15 years with at least one parity having stage 2 and above pelvic organ prolapse attending Gynecology OPD of BP Koirala Institute of Health Sciences, Dharan and the control were the women without prolapse with at least one parity in neighborhood matched with age. A total of 230 respondents (1 Case:1 Control) were included in the study. A semi structured interview was carried out to obtain the information for both groups. Bivariate analysis along with conditional logistic regression analysis was carried out to identify the association between selected variables with pelvic organ prolapse. Results: We found a significant association between age at first child birth (OR 1.98, CI 1.06-3.68), heavy load carrying during pregnancy (OR 3.97, CI 1.93-8.16), smoking (OR 3.49, CI 1.42, CI 8.61) and history of constipation (OR 3.57, CI 1.13-11.22) with pelvic organ prolapse. Conclusions: The finding showed that the significant factors for prolapse were age at first child birth, heavy load carrying during pregnancy, smoking and history of constipation. Keywords: Associated factors; case control study; matching; pelvic organ prolapse